MODERNISASI PERJANJIAN KERJA BERSAMA (PKB): INTEGRASI KLAUSUL HAK CIPTA SEBAGAI INSTRUMEN KEADILAN EKONOMI DAN KEPASTIAN HUKUM DALAM HUBUNGAN KETENAGAKERJAAN - Ruby W H Oktolina Samosir; Robert L Simanungkalit (Jurnal Humaniora & Sosial Sains, 2026)
Transforming the economy based on knowledge leads to redefining industrial relations as more than merely physical but also intellectual energy. This research explores the juridical and sociological challenges behind the redistributing of the economic value of IP generated by a worker in Indonesia. The urgency of this research was triggered by the plan to revise the Indonesian Labor Law by the Indonesian Parliament in March 2026. Using the normative-comparative legal research method, this study compares the Work Made for Work doctrine in the US with Arbeitnehmererfindergesetz system in Germany. The data obtained concludes that there is a lack of regulation that often causes the employer dominant position at worker-employer relations, which disregards the worker’s moral and economic right. As a solution, this research suggests an alternative academic script that calls for more power in CBA in three pillars: economic justice, legal certainty, and power balance between parties. The conclusion of this research encloses the idea that the labor law should enforce the CBA as a balance instrument that secures the equal benefit between workers and employer in quest of competitive and harmonious industrial climates.